VIKTIMISASI DALAM PROSES PERADILAN PIDANA (STUDI KASUS PERKOSAAN) - Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2015)
Legal protection to victims of crime adequately not only a national issue, but also internationally. The seriousness of the protection of victims of crime, can be seen from theestablishment of the Declaration Of Basic Principles of Justice For Victims of Crime And Abuse Of Power by the United Nations, as a result of the Seventh United Nations Conggres On The Prevention Of Crime And Treatment of Offender, which took place in Milan, Italy, in September 1985. in any case handling criminal law enforcement agencies (police, prosecutors) are often faced with the obligation to protect the two interests that seem contradictory, that the interests of victims should be protected to restore his suffering as it has become a victim of crime (mentally , physical and material), and the interests of the suspect/defendant even if he'sguilty, but he remains as human beings who have rights which should not be violated. The Code of Criminal Procedure (Criminal Code) has been set up for the protection of suspects / defendants more numerous than the protection of victims of crime. As a result, the rights of victims of crime receive less attention.